Management of Indian gypsy moth in dry temperate zone - Vashisth, Sumit; Gautam, Nidhish; Verma, Sudhir (Indian Horticulture, 2023)
Lymantria obfuscata Walker (Lepidoptera: Lymantriidae), commonly known as Indian gypsy moth is a serious pest of horticultural and forest trees such as apple, poplar, salix and seabuckthorn in dry temperate zone Spiti of Himachal Pradesh. They have a single generation per year with eggs as dormant stage for more than eight months. Initially the young larvae bite small holes on new leaves, complete defoliation and fruit damage by the larvae has been recorded in severely infested apple trees. In case of fruits, larvae scrap the skin and make holes. The badly damaged fruits fall off, while those which recover become deformed with scars on the skin. It is advisable to collect and destroy egg masses. The larvae can be trapped in gunny burlaps tied on tree trunk near ground level, and destroyed.